Patient‐reported outcomes in patients chronic viral hepatitis without cirrhosis: The impact of hepatitis B and C viral replication. (2nd July 2019) - Younossi, Zobair M.; Stepanova, Maria; Younossi, Issah; Papatheodoridis, George; Janssen, Harry L.A.; Agarwal, Kosh; Nguyen, Mindie H.; Gane, Ed; Tsai, Naoky; Nader, Fatema
Abstract: Background & Aim: Chronic infections with hepatitis B or C (HBV and HCV) are associated with adverse clinical outcomes and patient‐reported outcomes (PROs). The aim is to compare PRO scores in patients with chronic HBV and HCV without advanced liver disease before and after suppression/clearance of their infection. Methods: Patients with HCV and HBV infection prior to initiation of antiviral treatment and after viral suppression/eradication completed PRO questionnaires. Results: We included 132 patients with HBV and 132 matched patients with HCV. Baseline PRO scores were significantly higher in patients with HBV in the domains of Physical Functioning, Role Physical, Bodily Pain, Social Functioning, and Role Emotional of SF‐36, SF‐6D utility, Emotional and Fatigue domains of CLDQ, Presenteeism and total Work Productivity Impairment of WPAI:SHP in comparison to patients with HCV by 5.8%‐13.2% of a PRO score range (all P < 0.05). After viral suppression (HBV DNA < 20 IU/mL after 48 weeks of treatment for HBV) or eradication (SVR‐12 for HCV), only Physical Functioning and Role Physical scores remained higher in HBV by 6.7%‐9.9%, while other PRO scores became similar between HBV and HCV groups ( P > 0.05). The most prominent improvement of PROs in HCV was noted in Vitality, Emotional, Fatigue and Worry domains. In addition, General Health, Worry and Work Productivity scores were the most improved in HBV. Conclusions: Prior to treatment, PRO scores were lower in patients with HCV in comparison to HBV. After successful treatment, both groups of patients experienced improvement in some PRO domains confirming the positive impact of treatment.